THE MARKERS OF SUICIDAL RISK OF ADULTS’ SELF-HARM BEHAVIOR: THE RESULTS OF ANONYMOUS RESEARCH, WHICH HAD BEEN CARRIED OUT WITH USING THE GOOGLE-FORMS - Enikolopov, S.N.; Boyko, O.M.; Medvedeva, Т.Е.; Vorontsova, О.Yu.; Kazmina, O.Yu. (Modern Psychology, 2019)
Self-harm is widespread around the world. Often self-harm is accompanied by suicide behavior. All of these make urgent researching of the markers of a suicidal risk of adults’ self-harm behavior. Materials of this study include the data provided by 128 respondents (109 women, 19 men, age from 18 to 49). There is online anonymous survey using google-form. The questions about self-harm behavior and psychopathological symptoms had been asked. Non-parametric Mann-Witney test and Spearmen’s coefficient of correlation were used to statistical analysis of the data. There were identified the markers of a suicidal risk of adults’ self-harm behavior, which include: demonstrative behavior with public self-harm, difficulties with the emotionally closer relationships building, increase in frequency of use of the word “blood”
Keywords: suicidal risk; self-harm; self-injury; internet